(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Export development is a critical component of economic growth for many countries. It involves expanding the reach of domestic products into international markets, thereby increasing national income, creating jobs, and enhancing competitiveness. One of the pivotal factors that influence the success of export development is logistics services. Efficient logistics are crucial in ensuring that goods reach their destination in a timely and cost-effective manner. This article delves into the role of logistics services in export development, highlighting their importance, challenges, and strategies for improvement.